2017
DOI: 10.18632/oncotarget.15074
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of clock genes and cancer risk: a field synopsis and meta-analysis

Abstract: BACKGROUND:The number of studies on the association between clock genes' polymorphisms and cancer susceptibility has increased over the last years but the results are often conflicting and no comprehensive overview and quantitative summary of the evidence in this field is available.RESULTS: Literature search identified 27 eligible studies comprising 96756 subjects (cases: 38231) and investigating 687 polymorphisms involving 14 clock genes. Overall, 1025 primary and subgroup meta-analyses on 366 gene variants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 115 publications
(110 reference statements)
0
64
0
2
Order By: Relevance
“…A research reported that RORα may also contribute to the effect of an enhancer through binding to and activating the Pcp‐2(L7) gene promoter and structural gene in Purkinje cells . Finally, one study found that RORA rs7164773 SNP was involved in a statistically significant interaction between breast cancer risk and menopausal status . Taken together, these results suggest that RORA may be considered to function as a tumor suppressor gene, and its high expression may contribute to a good prognosis across multiple cancers, including CM.…”
Section: Discussionmentioning
confidence: 96%
“…A research reported that RORα may also contribute to the effect of an enhancer through binding to and activating the Pcp‐2(L7) gene promoter and structural gene in Purkinje cells . Finally, one study found that RORA rs7164773 SNP was involved in a statistically significant interaction between breast cancer risk and menopausal status . Taken together, these results suggest that RORA may be considered to function as a tumor suppressor gene, and its high expression may contribute to a good prognosis across multiple cancers, including CM.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, genetic variants of human clock genes have been shown to be associated with phenotypic differences, which could allegedly impact on disease processes, including cancer [72]. Moreover, the various biomarker rhythms of circadian function can be differentially altered by disease processes [73].…”
Section: Other Indicators Of Circadian Function Such As Cortisol or mentioning
confidence: 99%
“…Several studies have examined associations between circadian genes and different cancer sites, especially breast cancer, while studies on circadian genes in prostate cancer occurrence are scarce. To date, six studies have investigated associations between genetic variants in clock genes and prostate cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined associations between circadian genes and different cancer sites, especially breast cancer, while studies on circadian genes in prostate cancer occurrence are scarce. To date, six studies have investigated associations between genetic variants in clock genes and prostate cancer risk . Among those studies, three have only tested this association at the SNP level, while the others also evaluated the association at gene and pathway levels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation